Intravital microscopy of collective invasion plasticity in breast cancer - Olga Ilina; Leonard Campanello; Pavlo G. Gritsenko; Manon Vullings; Chenlu Wang; Peter Bult; Wolfgang Losert; Peter Friedl (Disease Models & Mechanisms, 2018)
Cancer invasion programs are adaptive by switching between metastatic collective and single-cell dissemination; however, current intravital microscopy models for epithelial cancer in mice fail to reliably recreate such invasion plasticity. Using microimplantation of breast cancer spheroids into the murine mammary fat pad and live-cell monitoring, we show microenvironmental conditions and cytoskeletal adaptation during collective to single-cell transition in vivo. E-cadherin-expressing 4T1 and E-cadherin-negative MMT tumors both initiated collective invasion along stromal structures, reflecting invasion patterns in 3D organotypic culture and human primary ductal and lobular carcinoma. Collectively invading cells developed weakly oscillatory actin dynamics, yet provided zones for single-cell transitions with accentuated, more chaotic actin fluctuations. This identifies collective invasion in vivo as a dynamic niche and efficient source for single-cell release.